Using Tensioned Pullout Tests to Determine the Bond-Slip Relationship and Splitting-Propensity of Reinforcements Used in Pretensioned Concrete Railroad Ties - Holste, Joseph R.; Peterman, Robert J.; Beck, B. Terry; Wu, Chih-Hang (Rural Railroad Safety Center, Kansas State University., 2021)
A study was conducted to evaluate the bond and splitting propensity characteristics of 12 different 5.32-mm-diameter prestressing wires used in the production of prestressed concrete railroad ties. Establishment of the bond-slip relationship of these wires at both transfer of prestress (transfer bond) and under flexural loading (flexural bond) was necessary to enable the accurate modeling of these ties using finite elements. Transfer bond and flexural bond of various indent patterns were tested using tensioned pullout tests. Specimens of various sizes with single or multiple wires were tested to determine the effects of cover and wire quantity on bond. Results from the testing program showed 1) the tensioned pullout tests could be used to predict the transfer length of prisms made with the same reinforcement, 2) the indent geometry depth and side-wall angle are good indicators of the likelihood of specimen splitting cracks, and 3) the importance of adequate concrete cover to eliminate potential splitting cracks.
Keywords: Wire Bond; Tensioned Pullout Tests; Bond Slip; Infrastructure; Railroad Ties; Prestressed Concrete